A study of the overnight use policy for reserve books in the U.P. Institute of Library Science - Moral, Reysa Celeste N.; Yang, Jackson V. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
The role of the library is to serve the educational and academic needs of its users especially the students. The ILS Library is among the many libraries in the University of the Philippines which seeks to uphold this vision. But how can the said library serve its users well if they are not in favor with the present library rules and procedures implemented particularly at the reserve section? One aspect of the current policies in the ILS Library reserve section that ILS students do not approved is the limited span of time allotted (overnight use). Students suggest to extend the time (overnight use) in borrowing books to satisfy their informational needs. Due to this situation, most students are not able to return the book on time and have to pay an overnight fine. For these students, the fines should be reduced to at least half of the present fines imposed which is five pesos per hour and fifty pesos per day. The ILS Library reserve section has limited copies of books which affect the borrowers as well as the librarian. The librarian should think of ways on how they can reproduce the book which are in demand. In connection with this, fifty students of the ILS served to support the study. Sixty (60) percent are not in favor of the present library rules and regulations of the ILS Library reserve section.
Request slips, lists of students with overdue books and reservation sheet for overnight use policy were gathered and collected for the Part two of the study which is the document analysis. The ratio of the number of time overdue over the number of times borrowed has been observed that during the month of February 2001 (0.07056) has the greatest equivalent of the ratio and November 2000 (0.0169) has the least number of overdues and books borrowed. It was proven that the subject area and on time/overdue status are independent.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Library circulation and loans